2020
DOI: 10.1097/mao.0000000000002798
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bone Conduction Implant Geometry Improve the Bone Fit in Mastoids of Children and Young Adults

Abstract: Objectives: In 2012 the first active bone conduction implant was introduced, but did not fit into the mastoids of some adults and many children. Thus, a geometry change of the transducer was proposed (BCI 602). In this study, we aimed to determine whether these changes improved the mastoid cavity fit of the implant in children and young adults. Design: We retrospectively analyzed computed tomography scans of 151 mastoids from 81 children and adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 31 publications
2
17
1
2
Order By: Relevance
“…The findings of Wenzel et al confirm that changes in the dimensions of the internal part of the BCI602 benefit patients in all age groups and with all indications. According to prior authors, placement of the BCI602 requires less bone removal than the BCI601, and "the newer BCI 602 transducer is more likely than its predecessor to be completely accommodated in the mastoid bone" [45]. In our experience, the flexible design and the transition between the receiver coil and the floating mass transducer makes it possible to properly position the implant even in difficult anatomical conditions.…”
Section: Discussionmentioning
confidence: 71%
“…The findings of Wenzel et al confirm that changes in the dimensions of the internal part of the BCI602 benefit patients in all age groups and with all indications. According to prior authors, placement of the BCI602 requires less bone removal than the BCI601, and "the newer BCI 602 transducer is more likely than its predecessor to be completely accommodated in the mastoid bone" [45]. In our experience, the flexible design and the transition between the receiver coil and the floating mass transducer makes it possible to properly position the implant even in difficult anatomical conditions.…”
Section: Discussionmentioning
confidence: 71%
“…Based on a retrospectively analyzed large cohort of children and young adolescents, Rahne et al described an (hypothetical) optimal form of the FMT as a truncated cone to fit in almost all mastoids [33]. In September 2019, the manufacturer introduced a follow-up model (BCI 602) in Europe, with reduced FMT dimensions, that improved the bone fit in mastoids of children and young adults [34]. However, in certain cases, like very young children, 3D virtual preoperative planning is still recommended [35].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies, help to predict the ideal implant size in children and determine the position of BI300, are rare. Although, especially in childhood, most common indication of BCIs are external ear canal/middle ear malformation and chronic otitis media; patients from non-otological cases were also selected to create an average population, similarly to other researcher groups [ 15 , 16 ]. The idea behind our patient selection (i.e., otological and non-otological cases together) was, that previous study of pediatric uni- and bilateral ear canal atresia patients indicated that neither age nor diagnosis of atresia reliably predict a lower chance of identifying adequate bone thickness at typical implant sites, and no significant difference in bone thickness was found on the affected site compared to non-affected side [ 17 ].…”
Section: Discussionmentioning
confidence: 99%